Корпоративна соціальна відповідальність як чинник європейської інтеграції України - Шевченко, О.В.; Shevchenko, O. (Східноєвропейський національний університет імені Лесі Українки, 2013)
Its also emphasized that efficiency of social responsibility policy realization depends directly form the tight co-operation within the triangle "authorities-business-community". Concluded that further work toward the adoption of corporate social responsibility strategy in Ukraine would move our country closer to european standards of life and help to increase the welfare of ukrainian community.
Corporate social responsibility is described in the article as the tool for sustainable development goals achievement
О.В. Шевченко, к.політ.н., доц. кафедри міжнародних комунікацій і комунікативних технологій Інституту міжнародних відносин Київського національного університету імені Тараса Шевченка (Україна, м.Київ)
Keywords: corporate social responsibility; european integration of Ukraine; the strategy of corporate social responsibility development